Comparative Effectiveness Of Ramipril Versus Losartan In Adults With Primary Hypertension: A Scoping Review - Ngurah Pradnya Wibawa, Putu; Putu Lia Juliantini, Ni; Luh Putu Serly Ekayanti, Ni (Indonesian Health Journal, 2026)
Hypertension remains one of the leading global risk factors for cardiovascular morbidity and mortality. Despite the availability of multiple antihypertensive drug classes, achieving optimal blood pressure control continues to be a major clinical challenge worldwide. This research aims to compare the efficacy of Ramipril and Losartan in the management of Primary Hypertension. This scoping review analyzed articles published between January 2006 and January 2026 from PubMed, ScienceDirect, OpenAlex, and DOAJ. Inclusion criteria included English-language observational studies addressing the efficacy of both antihypertensives. Four articles were selected after a rigorous screening process. Ramipril was more effective in reducing SBP and DBP, whereas Losartan was superior for EF and LV remodeling. Ramipril also increased GSH and total antioxidant status, while Losartan was more effective for metabolic and vascular remodeling biomarkers. Ramipril is commonly associated with adverse effects such as cough, whereas dizziness is more frequently reported with Losartan. Losartan has been shown to be more effective in hypertensive patients with left ventricular hypertrophy (LVH) and may also contribute to improvements in insulin resistance. Further head-to-head comparison studies are needed to guide optimal therapy.